Analysis of goal scoring in all continent soccer tournament / Mohd Faridz Ahmad, Sharifah Maimunah Syed Mud Puad and Aishah Nadirah Mohamed Alauddin - Ahmad, Mohd Faridz; Syed Mud Puad, Sharifah Maimunah; Mohamed Alauddin, Aishah Nadirah (Universiti Teknologi MARA, Perlis, 2020)
The objective of this study was to analyze and quantify the goals scored between first half and second half period in all continent soccer tournaments. This study performed quantitative study that examined 713 goals from 290 matches at seven different soccer tournaments been analyzed from FIFA official website, all continents official websites and by using the goals scoring highlights from YouTube. The results showed that majority of the tournaments score more goals during second half. According to tournament, Gold Cup 2019, World Cup 2018, EURO 2016, AFCON 2019, Copa America 2019 and lastly Asian Cup 2019 showed that more goals been scored during second half while in contrast only OFC Cup 2016 showed more goals had been scored in first half. As summary, as the time moving towards an end of the match, player’s fitness components, mental aspect and coach’s tactical become the main factor that needs to be focus by coaches and other coaching team as the players started to fatigue mentally and physically.